Regional Economic Outlook, October 2017, Middle East and Central Asia. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2017)
Oil exporters in the Middle East and North Africa, Afghanistan, and Pakistan region (MENAP) are continuing to adjust to lower oil prices, which have dampened growth and contributed to large fiscal and external deficits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet